The naming patterns of the Swati people living in the townships: a case study of kaMsogwaba - Ngobeni, Nkateko (My University, 2018)
Substantial attention has been given to Zulu onomastic patterns. However, Swati onomastic patterns have not been afforded sufficient attention. Hence, this study was developed as a means of bridging the gap that exists within Nguni onomastic patterns. The study explores Swati personal names in the area of kaMsogwaba, a former informal settlement situated approximately 29 kilometres from the city of Nelspruit, in Mpumalanga Province, South Africa. The study focuses on how the residents of kaMsogwaba Township use Swati personal names to embrace their culture and religion. kaMsogwaba is a religiously diverse area and thus provided rich information for the purpose of this study. The township comprises various social classes and is under the leadership of a chief, which indicates that much of the traditional culture is still prevalent in the area. Therefore, the information required for this dissertation was obtained by studying the township of kaMsogwaba, its people, their culture and traditions. African societies are communal. This implies that social structures such as culture and religion have an impact on naming patterns as people socialize and navigate through life. Social identity theory and identity theory are used to explain how culture and religion become involved in the naming process. The study was conducted from a qualitative perspective, while ethnography was the main method used for data collection.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in African Languages & Linguistics to the Faculty of Humanities, School of Languages, Literature and Media, University of the Witwatersrand, Johannesburg, 2018